The factors that drive non-gaming brands’ marketers to underutilize video ads in casual games : Underutilization of casual gaming as an advertising medium - Siltanen, Nicolas (My University, 2023)
This research investigates the factors influencing non-gaming brands’ marketers in Finland to underutilize video ads in casual games, aiming to unravel the perceptions, attitudes, and decision-making activities that guide their investment decisions. Despite the vast potential of casual gaming advertising, particularly for non-gaming brands, this medium remains underutilized in the Finnish market. The study commences with an exploration of casual games as a relatively new advertising medium, addressing misperceptions that are surrounding casual gaming as and advertising medium (CGAM). The central research question focuses on identifying the driving factors that drive non-gaming brands’ marketers to underutilize video ads in casual games. The theoretical framework incorporates Roger's Diffusion of Innovations theory, and explores the influences of experiences, social dynamics, individual characteristics, brand perception, target audience understanding, and Integrated Marketing Communications theory. The study adopts a qualitative research design, employing semi-structured interviews with five carefully selected participants from leading media agencies in Finland. Thematic analysis is applied to extract patterns and themes from the rich qualitative data, ensuring a systematic examination of participants' narratives. Results highlight the nuanced landscape of marketers' decision-making, revealing the pivotal role of experiences, both direct and indirect, in shaping attitudes. Individual decision-makers' characteristics and social dynamics within agencies emerge as influential, emphasizing the collaborative nature of decision-making. The brand's positive perception, especially in enhancing brand image, acts as a driving force for investment. However, misperceptions about the target audience, lack of comprehensive data, and the perceived relative advantage present notable barriers. In terms of piloting video ads in casual gaming, the study identifies the perception of positive influence and context overshadowing other factors, emphasizing the role of emotional responses and subjective perceptions in decision-making. In conclusion, the decision-making activities of non-gaming brands’ marketers in piloting video ads in casual games represent a multi-faceted interplay of experiences, individual characteristics, social dynamics, brand perception, target audience understanding, data availability, and perceived relative advantage. These insights provide a comprehensive understanding to guide marketers and casual gaming ad sellers in navigating the evolving landscape of casual gaming as an advertising medium in the Finnish market.
Keywords: marketing; media agencies; marketing channels; innovaatiot; attitudes; perceptions (mental objects); decision making; advertising; marketing communication; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|